1976
DOI: 10.1002/jbm.820100105
|View full text |Cite
|
Sign up to set email alerts
|

Surface hydroxylation of styrene–butadiene–styrene block copolymers for biomaterials

Abstract: This work pertains to the development of high strength elastomers potentially useful as nonthrombogenic cardiovascular prostheses. Triblock copolymers of the styrene-butadiene-styrene type have been subjected to surface hydroxylation via intermediate epoxides providing reactive sites at the surface for the subsequent coupling of heparin while retaining the unique mechanical properties of the SBS copolymers.Curves of hydroxyl content versus the copolymer film thickness demonstrated the effect of swelling in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Ishihara and Iwasaki et al [9][10][11][12][13] synthesized a copolymer of 2-methacryloyloxyethyl phosphorylchloline (MPC) and nbutyl methacrylate (BMA), which is similar to bio-membranes, and they found that the copolymer is the best excellent anti-thrombogenic material in the world, and SPUs coated the copolymer shows the improved blood compatibility. 14 Sefton et al 15 prepared a styrene-butadienestyrene tri-block copolymer (SBS), which has also excellent mechanical properties and is able to mold at melt state, grafted with hydrophilic heparin molecules on the poly(butadiene) (PB) domains of SBS. After approximately two decades, Yang et al 16,17 grafted vinyl pyridine by radiating ultraviolet light on the surfaces of PB domains of SBS cast film and found that this surface reduced the adhesion of protein molecules and resulted in good anti-coagulation property of blood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ishihara and Iwasaki et al [9][10][11][12][13] synthesized a copolymer of 2-methacryloyloxyethyl phosphorylchloline (MPC) and nbutyl methacrylate (BMA), which is similar to bio-membranes, and they found that the copolymer is the best excellent anti-thrombogenic material in the world, and SPUs coated the copolymer shows the improved blood compatibility. 14 Sefton et al 15 prepared a styrene-butadienestyrene tri-block copolymer (SBS), which has also excellent mechanical properties and is able to mold at melt state, grafted with hydrophilic heparin molecules on the poly(butadiene) (PB) domains of SBS. After approximately two decades, Yang et al 16,17 grafted vinyl pyridine by radiating ultraviolet light on the surfaces of PB domains of SBS cast film and found that this surface reduced the adhesion of protein molecules and resulted in good anti-coagulation property of blood.…”
Section: Introductionmentioning
confidence: 99%
“…Sefton et al15 prepared a styrene‐butadiene‐styrene tri‐block copolymer (SBS), which has also excellent mechanical properties and is able to mold at melt state, grafted with hydrophilic heparin molecules on the poly(butadiene) (PB) domains of SBS. After approximately two decades, Yang et al16, 17 grafted vinyl pyridine by radiating ultraviolet light on the surfaces of PB domains of SBS cast film and found that this surface reduced the adhesion of protein molecules and resulted in good anti‐coagulation property of blood.…”
Section: Introductionmentioning
confidence: 99%
“…The ratio of the surface hard to soft segments appears to be an important parameter in determining blood response. A number of researchers have examined the blood compatibility of ABA triblock polymers.10- 13 Okano et a/. 14 have proposed that the hydrophilic-hydrophobic balance between the blocks is the principal determinant of the thrombogenicity of these materials.…”
mentioning
confidence: 99%